Ocean Dynamics and Topographic Upwelling Around the Aracati Seamount - North Brazilian Chain From in situ Observations and Modeling Results - Silva, Marcus; Araujo, Moacyr; Geber, Fábio; Medeiros, Carmen; Araujo, Julia; Noriega, Carlos; Costa da Silva, Alex (Frontiers in Marine Science, 2021)
The hydrodynamics and the occurrence of topographic upwelling around the northern Brazilian seamount chain were investigated. Meteorological and physical oceanographic data collected under the REVIZEE-NE Program cruises around the Aracati Bank, the major and highly productive seamount in the area, were analyzed and used to force and validate simulations using the 3D Princeton Ocean Model (3D POM). The Tropical Water mass in the top 150-m layer and the South Atlantic Central Water (SACW) beneath it and down to a depth of 670 m was present. The thickness of the barrier layer varied seasonally, being thinner (2 m) during the austral spring (October–December) and thicker (20 m) during the austral autumn (April–June) when winds were stronger. The surface mixed and isothermal layers in the austral winter (July–September) were located at depths of 84 and 96 m, respectively. During the austral spring, those layers were located at depths of 6 and 8 m, respectively. The mean wind shear energy was 9.8 × 10–4 m2 s–2, and the energy of the surface gravity wave break was 10.8 × 10–2 m2 s–2, and both served to enhance vertical mixing in the area. A permanent thermocline between the 70- and 150-m depths was present throughout the year. The isohaline distribution followed an isotherm pattern of variation, but at times, the formation of low-salinity eddies was verified on the bank slope. The 3D POM model reproduced the thermohaline structure accurately. Temperature and salinity profiles indicated the existence of vertical water displacements over the bank and along the direction of the North Brazil Current, which is the strongest western boundary current crossing the equatorial Atlantic. The kinematic structure observed in the simulations indicated vertical velocities of O (10–3 m.s–1) in the upstream region of the bank during austral winter and summer seasons. During the summer, the most important vertical velocities were localized below the lower limit of the euphotic zone; while during the austral winter, these velocities were within the euphotic zone, thereby favoring primary producers.